Psychological Safety in Online Classrooms: A Study of Emotional Design Elements in Learning Management Systems - Anggun Wida Prawira (Journal of Paddisengeng Technology, 2025)
Background. The effectiveness of psychological safety in online learning environments is closely related to learners’ perceptions of emotional design elements in Learning Management Systems (LMS). Emotional design—such as interface aesthetics, tone of instructional messages, and supportive feedback—can shape learners’ sense of security, participation, and willingness to take academic risks. Therefore, it is important for educators and LMS developers to understand how different emotional design elements influence students’ psychological safety in virtual classrooms. Purpose. This quantitative study aimed to investigate the preferences of university students regarding ten commonly discussed emotional design elements in LMS that contribute to psychological safety. Specifically, it examined whether these preferences are influenced by four learner variables: digital proficiency level, first language (L1), online learning anxiety (OLA), and online learning enjoyment (OLE). Method. The study involved 288 undergraduate students from three cultural-linguistic contexts—Chinese, Japanese, and Korean—enrolled in online courses. Data were collected through a structured questionnaire and analyzed using appropriate statistical techniques to identify patterns and differences in learner preferences. Results. Findings indicate that, regardless of digital proficiency level, L1, OLA, or OLE, learners preferred more explicit emotional design strategies, such as clear instructional guidance, personalized supportive messages, and transparent assessment criteria. However, Korean undergraduates scored lower on several design elements (e.g., public recognition, open discussion prompts, animated interface elements) compared to other participants. Conclusion. This study has significant implications for online pedagogy and LMS design. Understanding learners’ preferences for emotional design elements can help educators and platform developers create psychologically safe online classrooms that enhance engagement, reduce anxiety, and promote positive learning experiences.